Copper Tape- Solar Cell-Based Electrical Circuit as STEM Learning Media to Improve Science Literacy and Creative Thinking Skills - Inandang, Siska Handayani; Prima, Eka Cahya; Agustin, Rika Rafikah (Perhimpunan Intelektual Muslim Indonesia, 2025)
By 2022, the ranking of Indonesian students' science literacy skills will improve from 70th to 64th, but the latest score is lower than before. In this research, the researchers use a mixed-methods embedded design. This study aims to describe the implementation and improvement of science and creative thinking skills in students following the introduction of a solar cell project in STEM learning using copper tape solar cells. The research sample consists of 40 junior high school students from a single experimental group. The data collection instruments include a pretest and a posttest to measure science literacy and creative thinking skills, as well as assessment rubrics to evaluate students' creativity. Implementing STEM copper tape-solar cell learning can improve students' science literacy skills, with an average n-gain of 0.4 in the medium category. Implementing STEM copper tape-solar cell learning can improve students' creative thinking skills, with an average n-gain of 0.5 in the medium category. Based on the MANOVA test, the provision of the STEM copper tape solar cell learning model as a whole can have a significant effect on science literacy, increased science literacy, creative thinking, and improved thinking.